2015
DOI: 10.1016/j.brachy.2015.02.200
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose-Rate Brachytherapy Is Superior to Dose-Escalated EBRT for Unfavourable Risk Prostate Cancer: The Results of the ASCENDE-RT* Randomized Control Trial

Abstract: tumour cell densities. The iterative local search approach increases the TCP to a target value whilst constraining the dose to the urethra below user defined dose/volume constraints. Results: Co-registration of the in-vivo mp-MRI with ex-vivo MRI is challenging with considerable effort needed in image acquisition and post processing to obtain the accuracy required for focal planning (Fig 1). An ensemble-based supervised classification algorithm, trained on textural image features, demonstrates a highly sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Data from the Androgen Suppression Combined with Elective Nodal and Dose Escalated Radiation Therapy (ASCENDE-RT) trial, which randomized 396 patients with intermediate- and high-risk prostate cancer to androgen deprivation therapy and external beam RT +/− brachytherapy, are currently maturing and will provide additional insights regarding RT dose intensification using brachytherapy. Early results, presented in abstract form, demonstrated that radiotherapy intensification via brachytherapy boost improves biochemical control rates at the cost of increased toxicity and without an improvement in overall survival 41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from the Androgen Suppression Combined with Elective Nodal and Dose Escalated Radiation Therapy (ASCENDE-RT) trial, which randomized 396 patients with intermediate- and high-risk prostate cancer to androgen deprivation therapy and external beam RT +/− brachytherapy, are currently maturing and will provide additional insights regarding RT dose intensification using brachytherapy. Early results, presented in abstract form, demonstrated that radiotherapy intensification via brachytherapy boost improves biochemical control rates at the cost of increased toxicity and without an improvement in overall survival 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Updated data from the MRC RT-01 trial, which was the largest study in included in the Viani meta-analysis and in which all patients received ADT, demonstrated that dose escalation improved biochemical progression free survival and freedom from the use of salvage ADT 42 . In the ASCENDE-RT trial, all patients received 12 months of ADT 41 Whether ADT is necessary in the context of dose-escalated RT is less clear. RTOG 0815 is investigating whether the addition of short term ADT to dose-escalated RT improves overall survival for patients with intermediate-risk disease.…”
Section: Resultsmentioning
confidence: 99%
“…A biochemical control and metastasis-free survival rate at 5 years of 94 and 98 %, respectively, was shown by Tselis et al 2013 who evaluated 351 localized prostate cancer patients treated with high-dose-rate (HDR) brachytherapy (Tselis et al 2013 ). Preliminary results demonstrated by the large multi-institutional ASCENDE-RT trial show similar long-term control for BT as a boost treatment with EBRT (Morris et al 2015a , b ). In addition to long-term survival benefits, BT also offers significant quality-adjusted life-years (QALYs) benefits over both EBRT alone and radical prostatectomy (RP), the surgical removal of the prostate (Hayes 2010 ; Steuten and Retel 2013 ).…”
Section: Introductionmentioning
confidence: 90%
“…This phenomenon, along with the rapid dose fall-off beyond the edge of the prostate, enables improved, localized dose escalation (Lee 2009 ). Several clinical studies demonstrate excellent long-term biochemical disease control rates across risk groups, for both permanent and temporary brachytherapy, and either alone or in combination with EBRT or androgen deprivation therapy (ADT) (Tselis et al 2013 ; Ishiyama et al 2014 ; Martinez et al 2010 ; Morris et al 2015a , b ; Hoskin 2012 ). A biochemical control and metastasis-free survival rate at 5 years of 94 and 98 %, respectively, was shown by Tselis et al 2013 who evaluated 351 localized prostate cancer patients treated with high-dose-rate (HDR) brachytherapy (Tselis et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in external beam radiation and image guidance, there is no escaping the physical, inverse square law benefits of an interstitial treatment for dose escalation. Three randomised trials have now shown a significant biochemical control benefit of a brachytherapy boost over external beam alone . The recently presented Canadian ASCENDE‐RT trial showed a 15% improvement in biochemical control when a seed brachytherapy boost was employed for patients with intermediate‐ and high‐risk disease .…”
mentioning
confidence: 99%